2017
DOI: 10.1038/s41467-017-00208-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the tick gut milieu by a secreted tick protein favors Borrelia burgdorferi colonization

Abstract: The Lyme disease agent, Borrelia burgdorferi, colonizes the gut of the tick Ixodes scapularis, which transmits the pathogen to vertebrate hosts including humans. Here we show that B. burgdorferi colonization increases the expression of several tick gut genes including pixr, encoding a secreted gut protein with a Reeler domain. RNA interference-mediated silencing of pixr, or immunity against PIXR in mice, impairs the ability of B. burgdorferi to colonize the tick gut. PIXR inhibits bacterial biofilm formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
143
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(147 citation statements)
references
References 73 publications
(107 reference statements)
3
143
1
Order By: Relevance
“…Ixodes scapularis harbors a diverse group of native microbes, ranging from viruses to bacteria [2]. These microbial communities influence the ability of B. burgdorferi and A. phagocytophilum to colonize and persist within the vector [3][4][5]. Microbial biofilms [6], generated by symbiotic relationships in arthropod hosts [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ixodes scapularis harbors a diverse group of native microbes, ranging from viruses to bacteria [2]. These microbial communities influence the ability of B. burgdorferi and A. phagocytophilum to colonize and persist within the vector [3][4][5]. Microbial biofilms [6], generated by symbiotic relationships in arthropod hosts [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial biofilms [6], generated by symbiotic relationships in arthropod hosts [7,8]. Borrelia burgdorferi and A. phagocytophilum colonization in I. scapularis is associated with changes in the taxonomic composition of the microbiota resulting in diffuse biofilms [3,4]. Tick gene expression is affected by B. burgdorferi and A. phagocytophilum infection in I. scapularis gut.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that spermidine is more abundant in human blood (9 lM) than putrescine (0.13 lM) (Wishart et al, 2007(Wishart et al, , 2009(Wishart et al, , 2013 and is the only polyamine available in the midgut of nymphal ticks. The availability of spermidine in the various hosts and vectors harboring B. burgdorferi and its selective transport strongly suggests that spermidine is the essential polyamine required by B. burgdorferi for survival (Narasimhan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%